2015
DOI: 10.1051/0004-6361/201525621
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting fast and slow propagating waves of the extreme-UV intensity in solar coronal plasma structures

Abstract: Context. From 06:15 UT to 08:15 UT on 2011 June 2, a toroidal filament located at the joint of two active regions, 11226 and 11227, appeared to perform two eruptions. During this phenomenon, fast and slow magnetoacoustic waves were detected to propagate simultaneously along a funnel coronal loop system of AR 11227. Aims. We aim to understand the relationship between fast and slow magnetoacoustic waves during their propagations and measure their properties, such as the propagating speed, path, amplitude, and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
2
22
1
Order By: Relevance
“…Rather, it is based on the relationship to other periodicities and comparison with those expected for known wave modes when realistic loop and plasma properties are assumed. Zhang et al (2015) reported an observation of a coronal funnel with SDO/AIA which demonstrates fast and slow waves propagating along the same field-aligned path, consistent with numerical simulations of Pascoe et al (2013b; Nisticò et al (2014). Measurement of the propagation speeds allowed the plasma-β to be estimated as approximately 0.01.…”
Section: Introductionsupporting
confidence: 59%
“…Rather, it is based on the relationship to other periodicities and comparison with those expected for known wave modes when realistic loop and plasma properties are assumed. Zhang et al (2015) reported an observation of a coronal funnel with SDO/AIA which demonstrates fast and slow waves propagating along the same field-aligned path, consistent with numerical simulations of Pascoe et al (2013b; Nisticò et al (2014). Measurement of the propagation speeds allowed the plasma-β to be estimated as approximately 0.01.…”
Section: Introductionsupporting
confidence: 59%
“…Thus, for low values of β, which are also observed in solar coronal plasma structures (e.g. β ≈ 0.01 [22]), for the electron plasma frequencies of about 0.4 GHz, typical periods of current sheet oscillations are a few microseconds. …”
Section: Discussionmentioning
confidence: 83%
“…Andries et al 2005;Srivastava et al 2013) or wave modes (e.g. Zhang et al 2015), spatial seismology using time series from different locations (e.g. Verth et al 2007;Pascoe et al 2009b), temperature data from multiple bandpasses (e.g.…”
Section: Discussionmentioning
confidence: 99%